Both sides now: evolutionary traits of antigens and B cells in tolerance and activation - Hong, Youngjae; Kwak, Kihyuck (Frontiers in Immunology, 2024)
B cells are the cornerstone of our body’s defense system, producing precise antibodies and safeguarding immunological memory for future protection against pathogens. While we have a thorough understanding of how naïve B cells differentiate into plasma or memory B cells, the early B cell response to various antigens—whether self or foreign—remains a thrilling and evolving area of study. Advances in imaging have illuminated the molecular intricacies of B cell receptor (BCR) signaling, yet the dynamic nature of B cell activation continues to reveal new insights based on the nature of antigen exposure. This review explores the evolutionary journey of B cells as they adapt to the unique challenges presented by pathogens. We begin by examining the specific traits of antigens that influence their pathogenic potential, then shift our focus to the distinct characteristics of B cells that counteract these threats. From foundational discoveries to the latest cutting-edge research, we investigate how B cells are effectively activated and distinguish between self and non-self antigens, ensuring a balanced immune response that defends against pathogenic diseases but not self-antigens.